1996
DOI: 10.1002/(sici)1096-8652(199607)52:3<135::aid-ajh2>3.3.co;2-j
|View full text |Cite
|
Sign up to set email alerts
|

Effects of density and of dehydration of sickle cells on their adhesion to cultured endothelial cells

Abstract: Abnormal adhesion of sickle cells to vascular endothelium may be a factor in the initiation of painful vaso-occlusive crisis. The sickle cell population contains an unusually large number of less dense reticulocytes that are known to be more adhesive than mature red cells, but there is contradictory evidence regarding the adhesiveness of dense sickle cells. We used a flow-based assay of adhesion to cultured human umbilical vein endothelial cells to test the properties of density fractions of sickle cells, prep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2000
2000
2008
2008

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…In addition to the decreased markers of hemolysis and increased hemoglobin concentrations that likely resulted from an improvement in the hydration state of the sickle erythrocyte, it is quite possible that the observed decrease in dense RBCs could provide further beneficial effects due to a reduction in the adhesivity of sickle RBCs to both the vascular endothelium and to the proteins of the subendothelial matrix. [14][15][16] Furthermore, because reticulocytes are particularly adhesive and express the integrin complex ␣ 4 ␤ 1 that binds to both fibronectin 17 and vascular-cell adhesion molecule-1, 18,19 it is conceivable that a decrease in circulating reticulocytes could also reduce the adhesion of sickle erythrocytes to the vascular endothelium.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the decreased markers of hemolysis and increased hemoglobin concentrations that likely resulted from an improvement in the hydration state of the sickle erythrocyte, it is quite possible that the observed decrease in dense RBCs could provide further beneficial effects due to a reduction in the adhesivity of sickle RBCs to both the vascular endothelium and to the proteins of the subendothelial matrix. [14][15][16] Furthermore, because reticulocytes are particularly adhesive and express the integrin complex ␣ 4 ␤ 1 that binds to both fibronectin 17 and vascular-cell adhesion molecule-1, 18,19 it is conceivable that a decrease in circulating reticulocytes could also reduce the adhesion of sickle erythrocytes to the vascular endothelium.…”
Section: Discussionmentioning
confidence: 99%
“…However, a previous study has demonstrated that the maximum plasma effect on sickle RBC-endothelial adhesion occurs in vitro at a 10% plasma dilution. 37 A static adhesion assay was performed for the erythrocyte-microendothelial adhesion experiments and relationships described. Although it has been suggested that RBC adhesion mechanisms identified under conditions of flow are of more pathophysiologic relevance, it has been also noted that this view does not give consideration to the fact that microvessel blood flow can be intermittent, 38 and that stasis may be enhanced by slowmoving and relatively large granulocytes or cellular aggregates, 39 thus simulating more closely adhesion assays where flow is absent.…”
Section: Discussionmentioning
confidence: 99%
“…Although the decrease in sickle erythrocyte adhesion to endothelial cells (Bridges et al , 1996), TSP and laminin and the decrease in integrin α 4 β 1 and CD36 expression (Styles et al , 1997) all preceded major increases in Hb F or F cells, most patients in these studies did have early increases in MCV, suggesting that cell volume may have an impact upon the adhesive phenotype. The hydration status of the erythrocyte has been reported to affect the adhesive phenotype of sickle erythrocytes to both endothelial cells (Hebbel et al , 1989; Francis et al 1991; Stone et al , 1996) and immobilized TSP and laminin (Punzalan et al , 1997), possibly by exposing or altering adhesive components of the erythrocyte membrane. A significant proportion of sickle red cells are inherently dehydrated, primarily because of intracellular K + and water losses via the erythrocyte Ca 2+ ‐dependent K + (Gardos) channel (Brugnara et al , 1986) and the K/Cl co‐transport system (Canessa et al , 1986).…”
Section: Discussionmentioning
confidence: 99%